CHAPTER 29 PLATE TECTONICS AND HEAVY MINERAL SUITES OF MODERN SANDS - Garzanti E.; Andò S. (My University, 2007)
This contribution classifies detrital heavy mineral assemblages produced in contrasting geodynamic settings, following the provenance scheme proposed by Dickinson and co-workers in the late 1970s. The vital link with bulk-sediment detrital modes was established by systematically coupling high-resolution heavy mineral and petrographic analyses on the same sample sets, in a series of actualistic provenance studies carried out in key geological areas, characterised by arid to semiarid climate. Quartzofeldspathic to quartzose sands of "Continental Block Provenance" contain either heavy-mineral-rich, hornblende-dominated assemblages derived from amphibolite-facies basements exposed along rift escarpments and in cratonic shields, or heavy-mineral-poor suites with commonly rounded ultrastable grains recycled from cover strata. Volcanic rifted margins shed lithofeldspathic detritus with clinopyroxene-dominated suites (largely lilac-brown Ti-rich augite) that commonly include olivine. Abundant clinopyroxenes (mostly green augite) and hypersthene, associated with olivine or dark-brown to reddish-brown hornblende (oxyhornblende), characterise feldspatholithic sands of "Magmatic Arc Provenance". The proportion of mainly blue-green hornblende increases progressively with erosion cutting deeper into the batholithic core of the arc massif. Quartzolithic sands of "Orogenic Provenance" include suites dominated by amphiboles, garnet, and epidote. The relative abundance of garnet (associated with subordinate staurolite, kyanite, and sillimanite) and blue-green to green-brown hornblende increases with increasing metamorphic grade of the sedimentary or igneous protoliths, respectively. Oman-type obduction orogens shed abundant heavy minerals, dominated by mafic and ultramafic minerals derived from the obducted ophiolite nappe. Apennine-type thin-skinned thrust belts provide heavy-mineral-poor assemblages recycled from accreted passive-margin successions or foredeep turbidites. Pyroxenes, derived from offscraped ophiolitic sequences, are locally present. The wealth of information heavy minerals provide on the geology of source areas makes their analysis an extremely powerful complementary tool in provenance studies of sediments not modified by diagenesis. © 2007 Elsevier B.V. All rights reserved.
Keywords: CONTINENTAL RIFTS; CRATONS; HEAVY MINERALS; MAGMATIC ARCS; OROGENIC BELTS; PLATE TECTONICS